KERJASAMA UNICEF DAN INDONESIA DALAM MENANGANI KEKERASAN ANAK DI INDONESIA TAHUN 2017-2020 - Fadillah, Diah; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research is about UNICEF's cooperation program in addressing child violence in Indonesia from 2017 to 2020. In response to an international phenomenon of child violence, UNICEF has proposed solutions through structured programs aimed at raising awareness and preventing violence against children within communities. In Indonesia, there were 11,735 reported cases of violence in 2017, with family being a primary contributing factor. The study collected data from academic journals, books, official documents, theses, and internet sources related to the issue of UNICEF's collaboration in addressing child violence in Indonesia from 2017 to 2020. The author utilized a pluralistic perspective and group analysis approach. The theoretical framework employed in this study was the theory of International Organizations. The research findings indicate that UNICEF effectively addressed child violence through several collaborative efforts with Indonesia. These include the Country Program Action Plan (CPAP), the Roots Program, UNICEF and Indonesia's efforts in the Love My Self campaign and #EndViolance, as well as the establishment of U-Report and Youth Partnerships. Keyword: Child Abuse, UNICEF, CPAP, ENDViolance